Role of Religio-Political Activism of TLP in Shaping Security Challenges for Pakistan - Ahmad, Sara; Falki , Sadia Mahmood (IUB Journal of Social Sciences, 2023)
ABSTRACT The substantial increase in support for conservative and far-right parties is a growing trend in South Asian politics. It is a part of emergent global tendencies of political polarization and the resultant rise of anti-democratic political forces around the world caused by diverse and unlike reasons. The subsequent outcomes of polarization propensities are steady societal discord and democratic erosion in both the global north and south countries. However, the adverse consequences of the rise of radical and far-right forces are comparatively more apparent in some of the South Asian states due to existing authoritarian traits in respective political systems and frequent political instrumentalization of religion into politics for the legitimacy of governments and regimes. In Pakistan, far-right parties remained less successful in electoral politics which led them to emphasize more on their ability to mobilize people in the name of religion in the form of agitation, protest, and violent demonstrations against the government. The display of radicalized discourses through street power often challenged the writ of the state and from time to time, these far-right groups like Tehreek-e-Labbaik (TLP) secured their bargaining position to pressure the government in Pakistan to overlook their violations of law and crimes to disturb law and order situation. The religio-political activism of far-right parties in Pakistan is deeply grounded in their discernment of an Islamic state which led them to see religion as an absolute authority over government and society while justifying their political power claims. The underlying study through the case study of TLP, tends to understand that how these religious political parties view the state and society in Pakistan. The emergence of TLP, its radical discourses, and the rise of gradual support to this religious party reflected the growing trend of polarization, anti-democratic trends, and its far-reaching consequences on national integration and most importantly in the larger context of the security of Pakistan.